Association of dietary phytochemical intake and the nutritional status of college students from the University of the Philippines – Diliman - Calalo, Roberto C., Jr; Cuerquis, Rondell Rey V.; Tuya, kate marthy S. (College of Home Economics, University of the Philippines Diliman, 2023)
Phytochemicals are non-nutritive components in plant-based food items. Intake of these compounds is linked to positive health outcomes. Currently, however, there is a need to explore the relationship between phytochemical intake and the nutritional status of Filipinos, especially university students who encounter life changes that can negatively impact their diet and, consequently, their health and nutritional status. The present study used regression analysis to determine the relationship between the dietary phytochemical index score and the nutritional status of college students (n=68) from UP Diliman. The study collected dietary data for three non-consecutive days and the BMI score of college students through online data collection strategies. Results revealed that most participants (70.59%) have a normal BMI. In contrast, the underweight and obesity classifications have the lowest frequency, each with five cases (7.35%). Also, the participants' average dietary phytochemical index (DPI) score and mean adequacy ratio (MAR) were 9.55% and 0.78, respectively. This MAR suggests that the participants met the average requirements of the six selected micronutrients. Moreover, a significant positive relationship was found between the participants' dietary phytochemical index score and the MAR. It suggests that with every increase in the DPI score, there is a 5.25 (p<0.05) increase in the likelihood of meeting the micronutrient requirements. Thus, it is suggested that incorporating phytochemical-rich foods in one's diet be increased to reduce the likelihood of micronutrient inadequacy. Furthermore, inclusion and emphasis on the importance of consuming colorful plant-based foods in nutrition education and counseling is also recommended.